1-Cos^2x=Sin^2x
1-sin^2x=cos^2x
tgx*ctgx=1
Sin^2x / Cos^2x + 1 = tg^2x +1 = 1/ Cos^2x
1. 1) -204/100 : 1/25 = -204/100 * 25 = -204/4 = -51
2) 361/100 : - 19/40 = - 361/100 * 40/19 = -38/5 = -760/100 = - 7,6
3) -51 +7,6 = -43,4
4) -434 / 10 : (-14/5) = -434/10 * (-5/14) = 31/2=15,5
5) 6/10 : (-9/10) = 6/10 * (-10/9) = -2/3
6) 155/10 - 2/3 = 465/30 - 20/30 = 445/30 = 14 5/6
2. 1)77/10 : (-11/40) = - 77/10 * 40/11 = -28
2) 38/10 : -1/20 = - 38/10 *20 = -76
3) -28+76 = 48
4) 48* -5/16 = -15
5) 4/10 : -36/100 = -4/10 * 100/36 = -10/9
6) -15 + 10/9 = -135/9 + 10/9 = -125 / 9 = -13 8/9
6х+х=28
7х=28
х=28/7
х=4
9х+5х=10+26
14х=36
х=36/14
х=2 целых 4/7